Influence of Genetic Variants in EGF and Other Genes on Hematological Traits in Korean Populations by a Genome-Wide Approach. (30th April 2015) - Kim, Yun Kyoung; Oh, Ji Hee; Kim, Young Jin; Hwang, Mi Yeong; Moon, Sanghoon; Low, Siew-Kee; Takahashi, Atsushi; Matsuda, Koichi; Kubo, Michiaki; Lee, Juyoung; Kim, Bong-Jo
Abstract : Hematological traits are important health indicators and are used as diagnostic clinical parameters for human disorders. Recently, genome-wide association studies (GWAS) identified many genetic loci associated with hematological traits in diverse ethnic groups. However, additional GWAS are necessary to elucidate the breadth of genetic variation and the underlying genetic architecture represented by hematological metrics. To identify additional genetic loci influencing hematological traits (such as hematocrit, hemoglobin concentration, white blood cell count, red blood cell count, and platelet count), we conducted GWAS and meta-analyses on data from 12, 509 Korean individuals grouped into population-based cohorts. Of interest is EGF, a factor plays a role in the proliferation and differentiation of hematopoietic progenitor cells. We identified a novel EGF variant, which associated with platelet count in our study (P combined = 2.44 × 10 - 15 ). Our study also replicated 16 genetic associations related to five hematological traits with genome-wide significance (P < 5 × 10 - 8 ) that were previously established in other ethnic groups. Of these, variants influencing platelet count are distributed across several genes and have pleiotropic effects in coronary artery disease and dyslipidemia. Our findings may aid in elucidating molecular mechanisms underlying not only hematopoiesis but also inflammatory and cardiovascular diseases.